HEALTH AS A CORE CHARACTERISTIC OF HUMAN EXISTENCE - A.G. Madzhuga (Journal of Global Pharma Technology, 2016)
Nowadays the humanity has reached the limits of its physical existence and such unprecedented impairment of harmonious relationships between nature and mind that it is impossible to keep neglecting natural biological foundations of a human body anymore, as split human integrity inevitably leads to the loss of his essential certainty and his disappearance.